2012
DOI: 10.1021/es203784u
|View full text |Cite
|
Sign up to set email alerts
|

Humic Acid Facilitates the Transport of ARS-Labeled Hydroxyapatite Nanoparticles in Iron Oxyhydroxide-Coated Sand

Abstract: Hydroxyapatite nanoparticles (nHAP) have been widely used to remediate soil and wastewater contaminated with metals and radionuclides. However, our understanding of nHAP transport and fate is limited in natural environments that exhibit significant variability in solid and solution chemistry. The transport and retention kinetics of Alizarin red S (ARS)-labeled nHAP were investigated in water-saturated packed columns that encompassed a range of humic acid concentrations (HA, 0-10 mg L(-1)), fractional surface c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
100
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(120 citation statements)
references
References 37 publications
(92 reference statements)
19
100
1
Order By: Relevance
“…This result is consistent with bacteria transport studies in various fractions of iron oxide-coated sands, 25,26 but a linear increase in k sw1 with λ has been reported for nanoparticles. 27,64 This discrepancy is likely related to differences in the size of the a IS was 1 mM KCl. The input concentration of MWCNT was 1 mg L −1 .…”
Section: 12mentioning
confidence: 99%
“…This result is consistent with bacteria transport studies in various fractions of iron oxide-coated sands, 25,26 but a linear increase in k sw1 with λ has been reported for nanoparticles. 27,64 This discrepancy is likely related to differences in the size of the a IS was 1 mM KCl. The input concentration of MWCNT was 1 mg L −1 .…”
Section: 12mentioning
confidence: 99%
“…The first kinetic Site-1 colloid , time-dependent retention, assumes reversible retention using first-order retention (k 1a ) and detachment (k 1d ) coefficients, and a Langmuirian approach blocking function (Adamczyk et al, 1994;Wang et al, 2012) to account for maximum soil colloid content on Site-1 colloid of sand (S max1 ). The second kinetic Site-2 colloid , depth-dependent retention, assumes irreversible retention using a first-order retention coefficient (k 2a ) and a depthdependent blocking function (Bradford et al, 2003;Wang et al, 2012). s 1 and s 2 are the retained colloid contents in column sand associated with Site-1 colloid and Site-2 colloid , respectively.…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…Due to the difficulty in distinguishing soil colloid from sand chipping, soil colloid retention in the sand columns was not measured in this study. However, the values of model fitting was employed to describe soil colloid retention in all columns (Sun et al, 2015b;Wang et al, 2012;Wang et al, 2013). The amount of retained soil colloids sharply decreased with increasing pH.…”
Section: Transport Of Soil Colloidsmentioning
confidence: 99%
“…Many researchers pointed out that taking into consideration of model-fitted parameters is vital to gain insight in understanding colloid deposition mechanisms (Wang et al, 2012;Gamerdinger and Kaplan, 2001;van Genuchten and Wagenet, 1989). They demonstrated that the breakthrough curves (BTCs) of colloids can be adequately fitted using a variety of models.…”
Section: Introductionmentioning
confidence: 99%